Aplicación de la metodología Tripod Beta modificada para el diagnóstico de las causas raíz de los problemas operacionales presentados en la perforación de los pozos K, L y M en el campo Castilla (2017)
The Tripod Beta Modified methodology allows the development of a root cause analysis of the operational problems in the drilling of oil Wells. To know these causes helps to decreases the economic costs and drilling times representing a saving for oil companies who can solve the problem in an immediate way with no danger of have the same problems in the future. The Castilla Field is the perfect scenary to apply the Tripod Beta Modified methodology and it allows Ecopetrol S.A. to understand the root causes of the operational problems in the field and to avoid them of happening in future wells.